Molecularly Imprinted Poly(glutamic acid) Modified Carbon Paste Electrode For Amperometric Determination of Ascorbic Acid - Ruhulkamil, Lu'lu'
Ascorbic acid is one of biological compound which is very important for our health. The high need of ascorbic acid in human body leads to the production of many ascorbic acid supplements. Therefore, it is important to have accurate analytical method to determine ascorbic acid. Amperometric method provides good sensitivity and selectivity for ascorbic acid determination. In this study, we investigated the molecularly imprinted poly(glutamic acid) modified carbon paste electrode (CPE) as working electrode for amperometric determination of ascorbic acid. The CPE was modified using cyclic voltammetry technique (6 cycles) from solution containing 10 mM glutamic acid and 5 mM ascorbic acid. The optimum pH of measurements was 5. Repeated measurements of 1 mM ascorbic acid in PBS pH 5 gave %RSD of 4.84% showing good precision of the method. The % RSD 1 mM of ascorbic acid oxidation current in PBS pH 5 obtained using 6 different modified working electrodes was 4.18% showing good reproducibility of the measurements. Linear range of calibration curve was found in the concentration range of 2 × 10-6 M – 8 × 10-4 M and the detection limit of 4.5 × 10-7 M. The accuracy of the method was good with percent recovery of 95.91 - 103.89%. Uric acid and dopamine does not interfere significantly to the oxidation current of ascorbic acid.